2020
DOI: 10.1111/jopr.13233
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Cast Gold and Ceramic Onlays Placed in a School of Dentistry: A Retrospective Study

Abstract: Purpose: This study was done to compare the survival rates of cast gold and ceramic onlays placed in a dental school setting. Material and Methods: An electronic search was conducted in the patient records at Adams School of Dentistry, University of North Carolina at Chapel Hill for onlay codes that were in the database (From 1998 until 2018). Progress notes and radiographs were scrutinized to establish the survival time of the restorations. Any complications that occurred during the life time of the restorati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The inter-rater reliability of the full-text screening between two independent researchers was rated as excellent, with a kappa statistic of 0.87 [ 24 ]. One eligible article could not be included due to the lack of detailed survival data [ 20 ]. Finally, 12 articles were included in the systematic review and meta-analyses (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inter-rater reliability of the full-text screening between two independent researchers was rated as excellent, with a kappa statistic of 0.87 [ 24 ]. One eligible article could not be included due to the lack of detailed survival data [ 20 ]. Finally, 12 articles were included in the systematic review and meta-analyses (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the declining patient acceptance of gold restorations [ 19 ], they are still widely used and the subject of ongoing clinical research [ 20 , 21 ]. However, increasing esthetic demands and changing indications among dentists have led to an increase in the use of tooth-colored materials instead of gold [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The risk of bias in the studies included was assessed by two calibrated examiners (VN, AJ) using quality assessment. [ 10 11 ]…”
Section: Eligibility Criteria and Study Selectionmentioning
confidence: 99%
“…Strasding evaluated the survival rate and the technical and biologic outcomes of all-ceramic onlay restorations in premolars and molars and indicated the overall 11-year survival rate of the onlay restorations was 80.0% [ 9 ]. And in study of Irusa showed the survival rate of ceramic onlay restorations were 81.1% for 6–22 years [ 10 ]. However, there is limited information available regarding the outcome and factors influencing the outcome of CAD/CAM onlay restorations [ 11 ].…”
Section: Introductionmentioning
confidence: 99%